Production of Bioethanol from Rice Straw Assisted by Cellulosic Enzyme Oyster Mushroom Stem Using Simultaneous Saccharification and Fermentation (SSF) - Tatang Shabur Julianto; M. Arsyik Kurniawan S; Ikhwan Arifin (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
Bioethanol is an alternative energy source to replace fossil fuels that can be produced from agricultural waste such as rice straw. The fermentation process can help hydrolyze lignocellulosic compounds in rice straw into simple sugars and convert them into bioethanol. This study aims to determine the effect of fermentation time and the amount of intracellular cellulase enzyme extract from oyster mushroom stem on the levels of biethanol produced. The method used in making bioethanol is Simultaneous Saccharification and Fermentation (SSF). The bioethanol produced was then analyzed by gas chromatography and UV-Vis spectrophotometer. The result showed that the highest level of bioethanol was 14.52% obtained at 10 days fermentation time and the amount of cellulase enzyme extract was 25 mL.